Moulting and Brooding patterns of the little spiderhunter (arachnothera longirostra) in Sarawak - Chin, Andrea Yen Fei. (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Little spiderhunter (Arachnothera longirostra) is a common Bornean bird that lives on lowland primary and secondary forest in both undisturbed and disturbed habitat. The annual cycle of moulting and brooding patterns by the Little spiderhunter is described. These are used to estimate the breeding season that fits into its annual cycle. Factors such as climatic patterns that influence their breeding season are analysed as well. The result showed that there is a distinct pattern between the amount of rainfall in relation with the breeding season of Little spiderhunter. The high amount of rainfall during the North-East (NE) monsoon season of Sarawak at the end till early of the year (November-February) flourish the plants that leads to the flowering and fruiting season during March and October. This increased the amount of food availability for nectarivorous species such as the Little spiderhunter. The population of frugivorous insects that feed on plant parts such as young leaves experience a population flush when the NE monsoon is over. Little spiderhunter that is known to be an opportunistic breeder took this conducive period as their breeding season on an annual cycle in Sarawak. This birds breeds from May to June, when the seasonal condition is conducive.